CONCEPTUAL PRINCIPLES OF SCHOOL OF PERSONALITY INCREASE: FROM CREATIVE SELF-REALIZATION TO PERSONALITY BECOMING (SEARCHES AND PROSPECTS) - Soldatenko, Olga (Educological discourse, 2019)
The article is sanctified to the search of methodological and didactics principles of design of development of the authorial pedagogical system. The authors of the article offer for consideration conceptual principles of the innovative educational system «Studio-dialogue» in relation to the prospects of development of individuality competense of life personality, intellectually free, that has aspiring to self-perfection and studies during life, high spirituality man with civil position, ready to the conscious vital choice and self-realization, professional activity and civil activity. A strategic aim and basic result of the innovative educational system «Studio-dialogue» is development of individuality competense of life personality, becoming of integral personality, action and the acts of that are determined by moral knowledge; to personality that owns the Ukrainian civil identity, by selective activity in her co-operating with a cultural and educational environment; by personality that is ready to the self-education, self-determination and to responsible behavior in the fleeting hi-tech competition multicultural world. The conceptual idea of School of personality increase answers the calls of time and creates the favourable mode of socialization of new generations. The system will nurse from strategy maintenance of cultural variety and unity of culture and decision-oriented the tasks put before education as social institute: providing of the civil world, social stability, economic development of Ukraine, that it is represented in her model. In the name of the educational system of School of personality increase a key for modern society concept is taken away is a «Studio-dialogue», that is interpreted as cooperation of different positions, presentations, ideas, characters, languages of sciences and arts, points of view, sent to arriving at mutual understanding of participants of dialogue; but as a method of cognition of the world, mastering of spiritual values, method of self-determination that allows to the man to learn to live in the conditions of variety of cultures, types of consciousness, looks.